The Study of Male-Female Chamfer Angle Effect on Aluminum 6061 Forging at Rotary Friction Welding Process - Yohanes Yohanes; Anugra Fikri Azmi; Ridwan Abdurrahman (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
This research aims to investigate male-female chamfer angle effect on forging pressure, specimen length and the maximum tensile strength in splicing 6061 aluminum material, which used the rotary friction welding process. This research employed the analytical method to determine the timing of forging pressure as an initial reference to conduct the experimental study for the specimens test. The specimens were tested by varying the male-female chamfer angle, namely 0°, 15°, 30°, 45°, 60°. The results test were obtained the longest application of forging pressure at the male-female chamfer angle of 60° and the fastest application of forging pressure at the male-female chamfer angle of 15°. The change in length of the specimen during the welding process for each variation of the male-female chamfer angle varies due to the friction time different. The largest change in length was at the male-female chamfer angle of 15° and the smallest change in length at the male-female chamfer angle of 60°. The maximum tensile strength was obtained at the variation of male-female chamfer angle of 60° with a value of 226.47 MPa.